Upaya Penanaman Nilai Moral Melalui Pendidikan dalam Keluarga - Sri Rahayu Pudjiastuti (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2009)
Abstract: The objective of this qualitative research is to investigate the improvement of quality of childrens’morality at Komplek Hankam Cimanggis Depok in family education. The results revealed that the quality of morality is family education which is accepted since childhood. Quality of morality knowledge must be introduced first to children in the family. As such, the family role is very important in giving quality of morality to children. The quality of morality includes these like good behaviors, mutual honor, mutual respect, honesty, generosity and considerateness.